Whoop-up Country : The Canadian-American West, 1865-1885 - Sharp, Paul F. (Paul Frederick), 1918-2009 (Book collections on Project MUSE., 1955)
Whoop-up Country was first published in 1955. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. In the frontier days before the railroads penetrated the western plains, the Whoop-Up Trail was a high road of adventure and commerce. It led Indians, traders, and cattlemen into a great interior market stretching northward from the Missouri River in Montana to the Bow River valley in the Canadian province of Alberta. From Fort Benton on the Great Muddy to Fort Macleod on the Oldman, the trail with the rowdy name wrote its history in whisky, guns, furs, and pioneer enterprise. But, as the Whoop-Up Trail faded away with the passing of the western frontier, people forgot about its existence and its part in the building of the West. Historians have largely overlooked this colorful chapter in the story of westward migration. Now Paul Sharp tells about the Whoop-Up country in vivid detail. By first describing the region geographically, he demonstrates an important pointthat there was no natural boundary in this area between Canada and the United States. He then relates the economic, social, and political events that ultimately divided the territory between the two nations in fact as well as in name. The volume contains an excellent account of the beginnings of the Northwest Mounted Police. It provides a fresh viewpoint on the Indian problem by considering it impartially and as a whole, without the restricting and artificial limitations of national boundaries. Told by a perceptive and forceful writer, this is the story of the creation of two societiesCanadian and Americanformed under similar circumstances yet developing very different political and cultural identities.